The correlation between Jun N-terminal kinase pathway-associated phosphatase and Th1 cell or Th17 cell in sepsis and their potential roles in clinical sepsis management - Yu, Dan; Peng, Xiaohong; Li, Peng (Irish journal of medical science, 2021)
Background We aimed to investigate the association between Jun N-terminal kinase (JNK) pathway-associated phosphatase (JKAP) and T helper type 1 (Th1) cell or Th17 cell, and their clinical values in sepsis patients. Methods Totally 125 sepsis patients and 100 healthy subjects as controls were included. Peripheral blood was extracted from each sepsis patient and each control, then serum and peripheral blood mononuclear cell (PBMC) were separated. JKAP and inflammatory cytokines were detected in serum by ELISA; Th1 cell or Th17 cell proportion was detected in PBMC using flow cytometry. Results JKAP level was downregulated while Th1 and Th17 cell proportions were upregulated in sepsis patients compared with controls. JKAP level negatively correlated with Th1 cell proportion in sepsis patients and controls, while was only negatively associated with Th17 cell proportion in sepsis patients but not in controls. In sepsis patients, JKAP level negatively associated with TNF-α, IL-1β, and IL-17 expressions. Meanwhile, JKAP level negatively but Th17 cell proportion positively correlated with acute physiology and chronic health evaluation II (APACHE II) and sequential organ failure assessment (SOFA) scores; however, Th1 cell proportion only positively associated with APACHE II score but not SOFA score. Additionally, JKAP level was reduced, while Th1 and Th17 cell proportions were increased in septic deaths compared with survivors. Multivariate logistic regression model disclosed that JKAP level and Th17 cell proportion independently predicted 28-day mortality. Conclusion Blood JKAP correlates with decreased Th1 and Th17 cells, also associates with reduced inflammatory cytokines, disease severity, and favorable outcome in sepsis patients.